Heritability, combining ability and inheritance of storage root dry matter in yam beans - Agaba, R.; Tukamuhabwe, Phineas; Rubaihayo, P.R.; Mwanga, Robert O.M.; Ssenyonjo, A.; Ndirigwe, J.; Tumwegamire, Silver; Grüneberg, W.J. (2017)
Storage root dry matter content (RDM) is central to the improvement of consumer and industrial attributes of root crops. Yam bean (Pachyrhizus species) is a legume root crop newly introduced in Uganda, but its adoption may be constrained by low RDM. The objective of this study was to investigate the magnitude of variance for general combining ability (GCA) and specific combining ability (SCA) effects, heritability estimates and inheritance of RDM in yam beans. Progenies of sixteen crosses, generated using the North Carolina (NCII) mating scheme, were evaluated in F1 and F2 field experiments, with three replications at the National Crops Resources Research Institute (NaCRRI), Namulonge in Central Uganda, during the first cropping seasons of April, 2013 and 2014, respectively. Significant (p<0.001) mean squares for general combining ability (GCA), and specific combining ability (SCA) were observed in F1 and F2 generations, demonstrating additive and non-additive genetic inheritance of RDM. High Baker’s ratio in F1 (0.76) and F2 (0.78), and large σ2GCA/σ2SCA (3.13) indicate predominance of additive gene effects. Narrow sense heritability was high in both F1 (0.74) and F2 (0.75), implying that RDM can be improved in yam beans through selection. The results provide a basis for selection of suitable parents for hybridisation and breeding programmes to develop high dry matter yam bean varieties in Uganda.